Pengaruh Seminar Online terhadap Pengetahuan Masyarakat tentang COVID-19 dan Adaptasi Kebiasaan Baru - Mariatul Fadilah; Pariyana Pariyana; Sisi Melansi; Ayu Kartika Putri (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; the existence of economic demands made the government try to find a solution by enacting a new order of life, namely the adaptation of new habits. Aim; knowing the effect of online seminars on people's knowledge about COVID-19 and the adaptation of new habits. Method; using a quasi-experimental pre and post-test design. The sample in the study of participants who filled out the pretest and posttest questionnaires were 181 respondents and the data were analyzed by univariate, bivariate, and Wilcoxon tests using the SPSS program. Results; shows that the majority of respondents have a median age of 25 years, gender is female (55.2%), the latest education is S1/D4 (65.2%), and most have a sufficient level of knowledge (42.5%), good (42,5% Conclusion: online seminars do not have a statistically significant effect in increasing public knowledge about COVID-19 and IMR but can still be considered as an alternative chosen for certain respondent characteristics.